Leadership styles of department heads and faculty behavior in selected technical vocational institutions in the National Capital Region and Region IV - Santos, Romula Loreta M. (1987)
The 46 department heads and 327 faculty members from 13 secondary and technical vocational institutions differed in their perceptions of the leadership styles of the department heads and of its relationship to faculty behavior. The following are significantly related to leadership styles of department heads: the department heads' age, sex, educational background and decision making pattern; faculty members' civil status, teaching experience and membership in professional organizations. Significantly related to faculty behavior are the department heads' attendance in inservice training, educational background, sex attitude, cooperative work, and decision making patterns; size of teaching force; and faculty members' educational background, sex, civil status, and teaching hours per week; and average class size. Faculty satisfaction with professional development, commitment to instructional improvement and participation in curriculum development varied significantly with the leadership style of the department heads; and the extent of faculty satisfaction, commitment and participation in decision making varied
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Leadership; School administrators; Teacher-administrator relationships -- Psychological aspects